Are U.S. consumers using MyPlate and restaurant menu labels and does their use equate with dietary and exercise behavior?. Issue 4 (30th March 2018) - Vaccaro, Joan A.; Huffman, Fatma G.
Abstract: The U.S. government provided a website, entitled MyPlate, and required menu labels to state calories to help the population make healthy dietary and exercise choices. The purpose of this study is to assess the awareness and use of nutrition information provided by MyPlate and by restaurant menu labels with dietary and exercise behavior for U.S. adults considering race/ethnicity and gender. This study uses data from the National Health and Nutrition Examination Survey 2013–2014 for adults, aged 20 years and older, from 3 racial/ethnic groups N  = 4924: 1, 275 Hispanics, 1, 177 non‐Hispanic Blacks (NHB); 2, 472 non‐Hispanic Whites to assess awareness and who reported seeing nutrition information at fast‐food/pizza places and waitstaff restaurants and answered affirmatively to hearing about MyPlate ( N  = 749). Dietary behaviors for controlling or losing weight, reducing fat, and increasing exercise was significantly higher for those who tried MyPlate as compared with those who stated they did not try MyPlate. Over half the individuals who reported that they tried MyPlate stated that they would often use nutrition information for fast‐food/pizza places and waitstaff restaurants as compared with less than one‐third of individuals who declared that they have not tried MyPlate. Males, Hispanics, NHB, individuals with a lower education level, current smokers, and older adults had higher percent of not hearing about MyPlate. NHB, males, and older adults had a lower percent of using menu nutrition information. Increasing use of MyPlate and menu calorie labeling may serve to encourage vulnerable groups to make healthy dietary and exercise choices.